Discrete Element Modelling (DEM) of Mine Backfill Deposition Within Narrow Wall - Ting, Wee Kiet; Alsidqi, Hasan (Springer, Singapore, 2026)
Mine stope is typically backfilled with Cemented Paste Backfill (CPB). The CPB provides a regional underground stability and also a reduction of aboveground tailings accumulation. During backfilling, a phenomenon known as arching occurs and affects the stress distribution of the CPB. The change in temperature due to uncontrolled heat transfer from the surrounding rock mass and/or generation from hydration process complicates the stress distribution development of CPB. This paper presents preliminary Discrete Element Modelling (DEM) simulation of backfill material within narrow wall which validates the speculated causes observed from experimental finding which leads to stress propagation anomaly. The main finding validated the behaviour of arching from a series of modification performed on the internal and interface friction of backfill material and its adjacent wall. The said frictional properties hold the key towards the stress behaviour throughout the backfilling, consolidation, and temperature changing phase. The coupled effects are proven to behave similarly towards both the experimental finding and full-scale investigation. This opens up the potential for further optimisation of DEM simulation in this area in order to improve mine backfill design at a lower research cost.